Collective action (still) matters: transformation of government social assistance mechanisms during the covid-19 pandemic - Aflah Faiz Rizqullah (Journal of Earth Kingdom, 2023)
This paper analyzed the Makassar government's public policy during the COVID-19 pandemic, namely the social assistance program. In this study, the perspective of stakeholders is taken, in which in this study the community is the main stakeholder. In addition, there are also other stakeholders such as the Social Service, District, sub District, Social Assistance Assistants. This research will explain the implementation of social assistance policies in Mariso District, Makassar and how the community responds to this policy. In addition, in this study, there were protests carried out by social assistance recipient communities in Mariso District, Makassar as a form of disappointment with the implementation of the Social Assistance policy in Mariso District, which proved successful enough to put pressure on so that aspirations and input could be realized and the government evaluated social assistance programs. COVID-19. This research conduct qualitative methods with data collection techniques using interviews with informants, in this case are the stakeholders. This study also uses the Stakeholder Mapping theory which was popularized by Eden, Ackermann and Bryson. This study uses 3 analyzes in this theory, namely 1) Power versus interest grid, 2) Problem-frame stakeholders map and 3) Policy implementation mapping. The Power versus interest grid is used by researchers to see and analyze from the side of interest and power for the community as the main Stakeholder in this research. The Problem-frame stakeholders map is used by researchers to see how the conditions of stakeholders, in this case, are the community. How does the community solve problems in this social assistance program and what actions are taken by the community to solve these problems. Policy implementation mapping is used by researchers to describe the strategies carried out by the community to influence social assistance policies, especially in Mariso District, Makassar.